Kajian Kualitas Jalan Pahlawan Sebagai Jalur Pejalan Kaki di Kota Semarang - Pattisinai, Amanda Ristriana (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
The aims of this study is to know the quality of Jalan Pahlawan as pedestrian ways. This study uses quantitative methods to determine the quality of pedestrian ways by considering several criteria PEQI (Pedestrian Environmental Quality Index) to be able to provide an assessment of the quality of the pedestrian ways wider choice to uses and diverse activities for pedestrians at Jalan Pahlawan. Analysis is conducted pedestrian activity analysis, user analysis based on age, gender and occupation, analyzes the quality of pedestrian ways cut by PEQI calculation and analysis of the quality of pedestrian ways based on the characteristics and activities of users. Road corridor represents a real picture of the image of a city where there is capacity to accommodate all forms of human mobility, one of which is a form of walking activity as the system actors. As one of the best pedestrian ways in Semarang today, Jalan Pahlawan has become a place for community activities. Nevertheless pedestrian ways not provide adequate quality for pedestrians. Number of pedestrian flows across very different intensity during the morning and evening, so the quality is still questionable and activities to meet the needs of its users.